1993
DOI: 10.1145/166962.167023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of trace sampling for performance debugging tools

Abstract: Recently there has been a surge of interest in developing performance debugging tools to help programmers tune their applications for better memory performance [2,4,10]. These tools vary both in the detail of feedback provided to the user, and in the runtime overhead of using them. MemSpy [10] is a simulation-based tool which gives programmers detailed statistics on the memory system behavior of applications. It provides information on the frequency and causes of cache misses, and presents it in terms of sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…A means to solve this problem is to limit the object of measurement. Effectiveness of Trace Sampling for Performance Debugging Tools [13] is a tracer in which the amount of data is reduced by focusing on memory access. In this system, memory accesses in the program that is the object of measurement are sampled, and the overall memory access performance is estimated by performing a simulation based on the obtained data.…”
Section: Related Studiesmentioning
confidence: 99%
“…A means to solve this problem is to limit the object of measurement. Effectiveness of Trace Sampling for Performance Debugging Tools [13] is a tracer in which the amount of data is reduced by focusing on memory access. In this system, memory accesses in the program that is the object of measurement are sampled, and the overall memory access performance is estimated by performing a simulation based on the obtained data.…”
Section: Related Studiesmentioning
confidence: 99%
“…Trace sampling was also mentioned as another and more sophisticated technique for reducing the trace size [14]. Instead of picking a trace of T consecutive references, the trace is split into a number of randomly located intervals within a larger trace.…”
Section: Speedup and Accuracymentioning
confidence: 99%
“…Several studies have demonstrated that sampling methods can bring significant speedups without loosing much accuracy [14,17,16]. However, they do not propose a simple and comprehensive method to control the associated accuracy issues; indeed, the accuracy decreases relatively quickly with the speedup since the principle is again to reduce the trace size in order to decrease simulation time.…”
Section: Introductionmentioning
confidence: 99%
“…After experimenting with various sample sizes and sampling ratios, we settled on a sample size of 500,000 references and a sampling ratio of 0.1. The process of tuning these parameters for a given workload is important [9,5]. The rationale for our choice for these Windows NT desktop application traces is briefly discussed in Appendix A.…”
Section: Sampling Techniquesmentioning
confidence: 99%
“…These demands can be greatly reduced by employing sampling techniques at the expense of providing only a statistical estimate of the properties of a full trace. Previous studies [9,6,5] contain results for other workloads and caches and discuss the conditions under which sampling may, or may not, be used.…”
Section: Introductionmentioning
confidence: 99%